Szándékok és körülmények a belgrádi konvencióval kapcsolatban - Takács, Gyula (Közép-Európai Közlemények, 2009)
In connection with the main questions of the Hungarian military politics in the autumn of 1918 this article focuses on the Hungarian related circumstances of the armistice of Padua and the Belgrade convention. Basically it tries to explain the Hungarian governmental intentions but it summarizes the French interests, too. It briefly reviews the arguments told by the Hungarian prime minister to the French commander of the Allied Army of the Orient in November 1918. It gives information about the difference between the French interpretation and Hungarian opinion as well. It also mentions a few factors about the Mackensen case and the first Hungarian governmental decisions. This article is an edited variant of a conference lecture.